Disruption of Glutamate Transport and Homeostasis by Acute Metabolic Stress - Passlick, Stefan; Rose, Christine R.; Petzold, Gabor C.; Henneberger, Christian (Frontiers in Cellular Neuroscience, 2021)
High-affinity, Na+-dependent glutamate transporters are the primary means by which synaptically released glutamate is removed from the extracellular space. They restrict the spread of glutamate from the synaptic cleft into the perisynaptic space and reduce its spillover to neighboring synapses. Thereby, glutamate uptake increases the spatial precision of synaptic communication. Its dysfunction and the entailing rise of the extracellular glutamate concentration accompanied by an increased spread of glutamate result in a loss of precision and in enhanced excitation, which can eventually lead to neuronal death via excitotoxicity. Efficient glutamate uptake depends on a negative resting membrane potential as well as on the transmembrane gradients of the co-transported ions (Na+, K+, and H+) and thus on the proper functioning of the Na+/K+-ATPase. Consequently, numerous studies have documented the impact of an energy shortage, as occurring for instance during an ischemic stroke, on glutamate clearance and homeostasis. The observations range from rapid changes in the transport activity to altered expression of glutamate transporters. Notably, while astrocytes account for the majority of glutamate uptake under physiological conditions, they may also become a source of extracellular glutamate elevation during metabolic stress. However, the mechanisms of the latter phenomenon are still under debate. Here, we review the recent literature addressing changes of glutamate uptake and homeostasis triggered by acute metabolic stress, i.e., on a timescale of seconds to minutes.